2013
DOI: 10.1016/j.jinteco.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Institution-driven comparative advantage and organizational choice

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To capture the quality of judicial institutions, we rely on survey information regarding the perceived corruption of the judicial system from the Varieties of Democracy Institute (see Pemstein et al, 2022). In an extension, we consider as an alternative the rule of law index from the Worldwide Governance Indicators (Kaufmann et al, 2010), which has been used for explaining the level and structure of bilateral trade flows in previous research (see Levchenko, 2007;Nunn, 2007;Ferguson and Formai, 2013). Beyond that, we also control for the share of preferential duty lines on inputs granted by the importer country to capture in a simple way the degree of bilateral integration prior to the formation of a TA, thereby acknowledging the qualification of our first hypothesis (see above).…”
Section: Empirical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To capture the quality of judicial institutions, we rely on survey information regarding the perceived corruption of the judicial system from the Varieties of Democracy Institute (see Pemstein et al, 2022). In an extension, we consider as an alternative the rule of law index from the Worldwide Governance Indicators (Kaufmann et al, 2010), which has been used for explaining the level and structure of bilateral trade flows in previous research (see Levchenko, 2007;Nunn, 2007;Ferguson and Formai, 2013). Beyond that, we also control for the share of preferential duty lines on inputs granted by the importer country to capture in a simple way the degree of bilateral integration prior to the formation of a TA, thereby acknowledging the qualification of our first hypothesis (see above).…”
Section: Empirical Analysismentioning
confidence: 99%
“…In Models 8 and 9, we consider alternative measures for the quality of (judicial) institutions. In Model 8, we rely on the rules of law index from the World Governance Indicators, which has been used by previous research as a proxy for the quality of judicial institutions in general and contract enforcement as well as the security of property rights in particular (see Levchenko, 2007;Nunn, 2007;Ferguson and Formai, 2013). Compared to our preferred measure, this variable has lower coverage of countries as well as time periods.…”
Section: B2 Robustness Checksmentioning
confidence: 99%
See 1 more Smart Citation
“…If institutions are of better quality, there will be a higher possibility of contracts being enforced. Ferguson and Formai [17] also state that "Institutional quality contributes to a country's comparative advantage in the same way as the more traditional sources such as factor endowments and technology." De Groot et al [18] found that institutional quality and the quality of governance have a significant, positive, and substantial impact on bilateral trade.…”
Section: Brief Literature Reviewmentioning
confidence: 99%